Advances in targeted therapy in non‐small cell lung cancer with actionable mutations and leptomeningeal metastasis. (26th July 2021) - Li, Ding; Song, Zhenguo; Dong, Bingqi; Song, Wenping; cheng, Cheng; Zhang, Yongna; Zhang, Wenzhou
Abstract: What is known and objective?: Leptomeningeal metastasis (LM) is a serious complication of advanced non‐small cell lung cancer (NSCLC) that is diagnosed in approximately 3%‐5% of patients. LM occurs more frequently in patients with NSCLC harbouring epidermal growth factor receptor (EGFR) mutations or anaplastic lymphoma kinase (ALK) rearrangements and is usually accompanied by a poor prognosis, with a median overall survival (OS) of several months if patients receive conventional treatments. However, tyrosine kinase inhibitor (TKI) therapy after LM diagnosis is an independent predictive factor for extended survival. Here, we aim to summarize the latest advances in targeted therapy for LM and provide patients with better treatment options. Methods: By reviewing the recent progress of targeted therapy in NSCLC with LM, especially the efficacy of newer generation TKIs, we aim to provide clinicians with a reference to further optimize patient treatment plans. Results and discussion: Osimertinib was confirmed to have a several‐fold higher CNS permeability than other EGFR‐TKIs and was recommended as the preferred choice for patients with EGFR‐positive LM whether or not they harboured the T790M mutation. Second‐generation ALK‐TKIs have a higher rate of intracranial response and can be positioned as front‐line drugs in NSCLC with LM. However, the sequence in which ALK‐TKIs are administered for effective disease control requires further evaluation. In addition, targeted therapy revealed a potential choice in patients with LM and rare mutations, such as ROS1 and BRAF. What is new and conclusions?: The development of therapeutic agents with greater CNS penetration is vital for the management of CNS metastasis from NSCLC, particularly in the EGFR‐mutant and ALK‐rearranged subtypes. Systemic therapy with newer generation TKIs is preferred as the initial intervention. This is because newer generation TKIs are designed to penetrate the blood‐brain barrier and possess significantly higher intracranial activities. However, their further effectiveness is limited by inadequate blood‐brain barrier penetration and acquired drug resistance. Further studies are needed to further understand the mechanisms underlying resistance to treatment. Abstract : The blood‐brain barrier prevents most therapeutic agents from accessing the cerebrospinal fluid (CSF). Inflow and outflow mechanisms jointly determine the drug's entry into the CSF. Newer‐generation TKIs have a higher CSF to blood concentration ratio.